The translation into “VIOLONÊS”: the transcription and arrangement process for the collection, “Ian Guest Music for Guitar (Orfeu, 2024)
This research offers a behind the scenes view of the collection “Ian Guest – Music for Guitar,” published in 2021 by Acervo Violão Brasileiro, focusing on the adaptation process for guitar. Ian Guest (1940-2022) had a significant role in the history of Brazilian music as a composer, musical director, arranger, and educator. His name is quite familiar due to his me-thods of harmony and arrangement, books that have been supporting the training of several musicians for decades. His produc-tion as a composer, however, is not as well known, gaining more visibility only recently through the publication of his “Songbook” (2019c), by Vitale, and the release of his only original album, “HEMATHACAMA” (2021g). But his catalogue, which dates back from the 1960s, gathers a considerable num-ber of works, including original pieces for guitar, songs, and chamber music, revea-ling the plurality of an intense musical life. Thus, in the same way that Hungarian Já-nos Geszti needed to translate his native language when he arrived in Brazil in 1957, his music went through something similar when transported to the guitar. Based on selected pieces that comprise the collec-tion, this process, done in collaboration with the composer, will be described in detail below
Keywords: Ian Guest; Brazilian guitar; transcription; arrangement; translation